تنظيم مهنة محافظ الحسابات في الجزائر في ظل معايير التدقيق الجزائرية - تجاني صهيب; ضياء قده; محمد الامين بوزيدي; محمد الامين قاسمي (جامعة الوادي university of eloued, 2024)
تهدف هذه الدراسة الى معرفة كيفية تنظيم مهنة محافظ الحسابات في الجزائر في ظل معايير التدقيق الجزائرية وذلك من خلال تقييم ومعرفة مدى مواكبة محافظ الحسابات للمحطات التي مرت بها هاته المهنة وما جاء فيها وتسليط الضوء على اهم جوانب هذه الدراسة واهم ما جاء فيها من قوانين وما تخللت هذه القوانين من قرارات تنظم هذه المهنة من مفهوم وهيئات وشروط المزاولة والمسؤوليات وكذا الواجبات التي تسهر على سيرورتها، وصولا الى التحول الجذري الذي اوصلنا الى اصدار معايير التدقيق الجزائرية لاستكمال ما جاءت به القوانين وابراز مستوى الارتباط بينها وبين الاحكام السابقة، كل هذا بالنظر لأهمية مهنة محافظ الحسابات لدى المشرع الجزائري والتي في الأخير تساهم في اتخاذ قرارات المستخدمين بعد مصادقة المحافظ على القوائم المالية، وفي سبيل تحقيق اهداف الدراسة باستخدام المنهج الوصفي ومن ثم تصميم استبيان وتوزيعه على أساتذة ومكاتب في مجال المحاسبة وتحليلها بواسطة برنامج SPSS وصولا للنتائج المطلوبة. This study aims to know how to organize the profession of bookkeeper in Algeria in light of the Algerian auditing standards, by evaluating and knowing the extent to which the bookkeeper keeps up with the stages that this profession has gone through and what was mentioned in it, and highlighting the most important aspects of this study and the most important laws and regulations that were mentioned in it. These laws include decisions that regulate this profession in terms of the concept, bodies, and conditions of practice and responsibilities, as well as the duties that ensure its progress, leading to the radical transformation that led us to issuing the Algerian auditing standards to complete what the laws brought and highlight the level of connection between them and previous provisions. All of this is in view of the importance of the profession of governor. The accounts are held by the Algerian legislator, which ultimately contributes to users’ decision-making after the governor approves the financial statements. In order to achieve the objectives of the study, a questionnaire was designed and distributed to professors and offices in the field of accounting and analyzed using the SPSS program to reach the required results.
مذكرة ماستر
Keywords: محافظ الحسابات، الغرفة الوطنية، معايير التدقيق الجزائرية، التشريع الجزائري، القوائم المالية، المجلس الوطني للمحاسبة; Governor of Accounts; National Chamber; Algerian auditing standards; Algerian legislation; financial statements; National Council of Accounting